Calculez : (-3)+(+5) / (-4)-(-3) / (-2.5)+(+1.2) / (+4.1)-(+8) Simplifiez et Calculez : (+2)-(-3)+(-5)+(+4)-(+2) / (16.7)-(-3.2)+(+4.8)-(+3.3) Calculez : 12-6+5 / 24-6:2 / 5x[4+(2+3x6)] / 42-4x9 Calculez en respectant les règles de propriété : (+7)-(-3+5)+(4-(-3)) / (-2)-[2-(-3+5)]

2

Réponses

  • Utilisateur Brainly
2013-06-23T17:04:54+02:00

Calculez :

(-3)+(+5) =2

 

(-4)-(-3) =-1

 

(-2.5)+(+1.2) =-1,3

 

(+4.1)-(+8)=-3,9

 

Simplifiez et Calculez :

(+2)-(-3)+(-5)+(+4)-(+2)=-4

 

(16.7)-(-3.2)+(+4.8)-(+3.3)=6,4

 

Calculez :

12-6+5=11

 

24-6:2=21

 

5x[4+(2+3x6)]=120

 

42-4x9=29

 

Calculez en respectant les règles de propriété :

(+7)-(-3+5)+(4-(-3)) =12

 

(-2)-[2-(-3+5)]=-2

2013-06-23T18:00:57+02:00

Calculez :

 

(-3)+(+5)  =2

 

(-4)-(-3)  = -4+3

              =  -1

 

(-2.5)+(+1.2) =  -1.3

 

(+4.1)-(+8) =  4.1+(-8)

                  = -3.9

 

Simplifiez et Calculez :

 

(+2)-(-3)+(-5)+(+4)-(+2)= 2+3+(-5)+4+(-2)

                                     = 9+(-7)

                                     = 2

 

(16.7)-(-3.2)+(+4.8)-(+3.3)= 16.7+3.2+4.8+(-3.3)

                                          = 24.7+(-3.3)

                                          = 21.4

 

Calculez :

 

12-6+5= 6+5

           = 11 

 

24-6:2 = 18:2

           = 9

 

5x[4+(2+3x6)] = 5x [4+(2+18)]

                       = 5x (4+20)

                       = 5x24

                       = 120

 

42-4x9=42-36

           = 6

 

Calculez en respectant les règles de propriété :

 

(+7)-(-3+5)+(4-(-3))= 7-2+7

                              = 12

 

 (-2)-[2-(-3+5)]= -2- [-2-2]

                      = -2-(-4)

                      = -2+4

                      = 2